PERUBAHAN PENGGUNAAN LAHAN DI KOTA AMBON TAHUN 2002 - 2009 - , Mohammad Amin Lasaiba, S.Pd.,M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This research is aimed at analysing changes of land use in 2002 and 2009 in Ambon city, analysing the factors cause of its and assessing the deviation of land use on The Spatial Planning (RTRW). This research uses an interpretative and survey method are obtained from satellite imagery, field observations and relevant agencies. The sampling area based on probability sampling and for resident to use non-probability sampling. Techniques of data analysis in this study were analyzed spatially and statistically Results showed that change of land use in Ambon city during the period 2002 to 2009 covering an area of 919.675 ha (2.84%). In general, changes in land use has led to increased settlement and agricultural activities and most of causing reduction of mixed farms and areas which suffered damage due to social conflicts. These reductions also occurred in forest land, bush, vacant land. Based on the factors that cause changes in land use, factor of accesibility, population, facilities and utilities, and political, influence on changes in land use. This is due to the security of Ambon city more conducive of social conflict so that more intensive development activities. While the land of physical factors (slope and elevation), initiative of developers, land ownership and regulations, does not affect land use change. Deviation of land use based on 2008 - 2028 regional spatial planning, in protected areas reached 52.812 ha and cultivated area, covering an area of 1346.692 hectares. The deviation is caused by settlement activity and as a result of limited land, and an increase in population and the impact of social conflicts that led to many scattered settlements in protected areas like the Air Besar Forest, Gunung Nona Forest and Sirimau Forest. Next to the development of neighborhoods based on Spatial planing, the point on land that has not occupied an area of 1645.961 hectares and generally can accommodate the needs of land to population in each village by the year 2029, amounting to 424,205 lives.